Building Solidarity in the Slow Food Movement - Shawki, Noha; Hunter, Gina L. (The International Journal of Sociology of Agriculture and Food, 2022)
Collective transnational efforts to create a more just, sustainable, and peaceful world must confront diversity and inequities associated with differential position and power. How movements deal with social disparities among participants impacts movement persistence, legitimacy, and efficacy. Slow Food International is a transnational movement that envisions good, clean, and fair food for all. Slow Food’s mobilization takes various forms across the globe, and its millions of participants are highly diverse in terms of race, ethnicity, national origin, and other dimensions of identity. In this article, we use the framework of active solidarity to consider how the international Slow Food movement has mobilized its diverse participants across global disparities and with what implications. Between 2018 and 2021 we conducted semistructured interviews with 24 movement leaders, Slow Food staff, and representatives from international development partners. Drawing on these interviews we consider the specific discourse, practices, procedures, and organizational structures that the Slow Food movement has used to address inequities and center the identities and experiences of marginalized communities. The Slow Food case provides an example of how civil society groups might adopt processes and practices that will not only deepen solidarity and inclusion, but also position them to realize their goals. Drawing on interviews with Slow Food leaders and partners from different parts of the world, this article considers the ways in which the aspiration to build solidarity and an inclusive movement is reflected in the discourse, practices, procedures, and organizational structures of the Slow Food movement. In addressing these issues, this article provides perspectives on how the identities and experiences of marginalized communities could be centered in the global food movement and how civil society-led efforts to build a more just and sustainable food system might adopt processes and practices that will not only deepen solidarity and inclusion, but also position the movement to realize its goals.